Corroboration, consent and community: a “meaning finitist” account of the forensic medical examination of rape and penetrative sexual assault complainers in Scotland - Rees, Gethin (The University of Edinburgh, 2009)
This thesis examines the construction of forensic medical evidence in penetrative sexual assault cases and the procedures that Forensic Medical Examiners (FMEs) employ in order to ensure the authority of that evidence. Drawing upon interviews and on the texts and artefacts that FMEs use in their work, the thesis employs the concept of “meaning finitism” to analyse how FMEs perform forensic examinations for evidential purposes. The thesis starts with an exploration of how medical practitioners are taught to identify and classify injuries of medico-legal significance, culminating in their being judged “safe” to provide expert testimony by other members of the clinical forensic medical community. The thesis next addresses the construction of what I call the “morphological account”: a set of judgements about the nature of a case based upon a combination of the observed injuries, the FME’s training and their previous experience of cases. While there is considerable agreement amongst practitioners about how to interpret injuries (a result of their training), because the morphological account involves personal judgement, there is also scope for differences of opinion. The thesis therefore explores the methods that FMEs employ to limit the risk of being seen to disagree with one another during trials. The thesis also examines the role that guidelines play in the forensic medical examination. The thesis argues that standardised medical kits and associated guidance documents were originally introduced in the early 1980s in response to sustained criticism of FMEs’ practices, and further developed in the late 1990s and early 2000s with the rise of Evidence-Based Medicine. Kits and guidance documents provide a means for FMEs to legitimate and explain their work to others, particularly during trials: they codify collective practice and provide FMEs with an aide memoire of the requisite procedures, without overly determining or constraining practice. Finally, I will argue that FMEs’ concern to ensure the authority of their evidence may sometimes limit the value of that evidence. Caution over drawing inferences that might be challenged in court, and a concern not to be seen as “prosecution-minded”, commonly leads FME to compose so-called “Neutral Reports” which neither confirm nor deny the complainer’s allegations. As Scottish Procedural Law makes provision for non-contentious evidence to be removed from trial, such neutral reports are likely to be dismissed from consideration.
Keywords: rape; strong progamme; evidence-based medicine; forensics; diagnosis; classification; injuries; training